In-vitro maturation of oocytes recovered during cryopreservation of pre-pubertal girls undergoing fertility preservation. Issue 5 (November 2020) - Fouks, Yuval; Hamilton, Emily; Cohen, Yoni; Hasson, Joseph; Kalma, Yael; Azem, Foad
Abstract: Research question: In-vitro maturation (IVM) of oocytes recovered during ovarian tissue cryopreservation (OTC) is often practised, although it is still considered experimental. To date, only a few studies have examined the success of this maturation process in pre-menarche girls. The aim of this study was to examine the outcomes of IVM of oocytes recovered during OTC in pre-menarche patients scheduled for onco-therapy. Design: A retrospective cohort study in a tertiary university-affiliated hospital. A total of 93 patients aged 0–25 years who underwent OTC as part of onco-fertility preservation between 2007 and 2019 were included in the study. Oocytes were recovered from the medium after OTC and matured over 48 h. Oocyte development and maturation rate were recorded and compared between different age groups. Results: Patient's age was not correlated linearly with the total number of mature oocytes R = 0.2. The absolute maturation rate in post-menarche and pre-menarche patients differed significantly (38.0% versus 25.3%, respectively; P > 0.001), whereas the degeneration rate of the oocytes did not (39.8% versus 33.5%; P = 0.167). The pre-menarche group had significantly lower mean number of metaphase II oocytes compared with the post-menarche group (2.8 [±2.3] versus 5.6 [±4.6]; P = 0.01; 95% CI –4.62 to –0.46). Oocytes recovered from patients aged 1–5 years demonstrated low maturation rate. Conclusions: Oocytes recovered from pre-menarche girls, and especially those younger than the age of 5 years who undergo fertility preservation, have a lower chance of reaching maturity in IVM compared with older women. This may indicate a need for alternative methods for preserving fertility in these young patients.